Performance analysis of P-wave detection algorithms for a community-engaged earthquake early warning system - a case study of the 2022 M5.8 Cook Strait earthquake - Chandrakumar, Chanthujan; Tan, Marion Lara; Holden, Caroline; Stephens, Max T.; Prasanna, Raj (New Zealand journal of geology and geophysics, 2025)
Can a P-wave detection algorithm enhance the performance of an Earthquake Early Warning System (EEWS), particularly in community-engaged networks of low-cost ground motion sensors susceptible to noise? If so, what P-wave detection algorithm would perform the best? This study analyses the performance of four different P-wave detection algorithms using a community-engaged Earthquake Early Warning (EEW) network. The ground motion data from a 48-hour time window around a M5.8 earthquake on 22 September 2022 were used as the basis for this case study, where false and missed detections were analysed for each P-wave detection algorithm. The results indicate that a wavelet transformation-based P-wave picker is the most suitable algorithm for detecting an earthquake with minimal missed and false detections for a community-engaged EEWS. Our results show that a citizen seismology-based EEWS is capable of detecting events of interest to EEW when selecting an appropriate earthquake detection algorithm. The study also suggests future research areas for community-engaged EEWSs, including dynamically changing P-wave detection thresholds and improving citizen seismologists' user experience and involvement.